E47 as a novel glucocorticoid-dependent gene mediating lipid metabolism in patients with endogenous glucocorticoid excess - Zhang, Wei; Nowotny, Hanna; Theodoropoulou, Marily; Simon, Julia; Hemmer, Charlotte M.; Bidlingmaier, Martin; Auer, Matthias K.; Reincke, Martin; Uhlenhaut, Henriette; Reisch, Nicole (Frontiers in Endocrinology, 2023)
Purpose: E47 has been identified as a modulating transcription factor of glucocorticoid receptor target genes, its loss protecting mice from metabolic adverse effects of glucocorticoids. We aimed to analyze the role of E47 in patients with endogenous glucocorticoid excess (Cushing's syndrome CS) and its association with disorders of lipid and glucose metabolism. Methods: Prospective cohort study including 120 female patients with CS (ACTH-dependent = 79; ACTH-independent = 41) and 26 healthy female controls. Morning whole blood samples after an over-night fast were used to determine E47 mRNA expression levels in patients with overt CS before and 6-12 month after curative surgery. Expression levels were correlated with the clinical phenotype of the patients. Control subjects underwent ACTH stimulation tests and dexamethasone suppression tests to analyze short-term regulation of E47.Results: E47 gene expression showed significant differences in patients cohorts with overt CS vs. patients in remission (p = 0.0474) and in direct intraindividual comparisons pre vs postsurgery (p = 0.0353). ACTH stimulation of controls resulted in a significant decrease of E47 mRNA expression 30 minutes after i.v. injection compared to baseline measurements.Administration of 1 mg dexamethasone overnight in controls did not change E47 mRNA expression. E47 gene expression showed a positive correlation with total serum cholesterol (p = 0.0036), low density lipoprotein cholesterol (p = 0.0157) and waist-arm-ratio (p = 0.0138) in patients with CS in remission.E47 is a GC-dependent gene that is upregulated in GC excess potentially aiming at reducing metabolic glucocorticoid side effects as dyslipidemia.